Magnetic resonance imaging and ultrasound evaluation of "healthy" joints in young subjects with severe haemophilia A. (18th March 2013) - Di Minno, M. N. D.; Iervolino, S.; Soscia, E.; Tosetto, A.; Coppola, A.; Schiavulli, M.; Marrone, E.; Ruosi, C.; Salvatore, M.; Di Minno, G.
Summary Magnetic resonance imaging (MRI) and ultrasonography (US) are increasingly used in haemophilia A (HA) to detect early joint changes. A total of 40 clinically asymptomatic joints, never involved by bleeding events ["healthy joints" (HJ)], were evaluated by MRI and, in parallel, by US in 20 young subjects with severe HA (22.45 ± 2.72 years old; no history of arthritides, of viral infections or of inhibitors against factor VIII). The same joints were evaluated in 20 matched non‐haemophilic (no‐HA) subjects (mean age 23.90 ± 2.31 years, P = 0.078 vs. HA subjects). US images were obtained with specific probe positions according to validated procedures. A validated US score and progressive (P‐MRI) and additive (A‐MRI) MRI scores were employed for data collection and analysis. The US score was higher in HA than in no‐HA subjects (3.40 ± 1.72 vs. 0.80 ± 1.10, P < 0.001). Taking into account only moderate/severe alterations, joint effusion was found in 55% of HA and in 5% of no‐HA joints (P < 0.001); synovial hypertrophy was found in 20% of HA and in none of the no‐HA joints; cartilage erosion was found in 30% of HA and in none of no‐HA joints. MRI examinations confirmed these findings and the US score correlated with the A‐MRI (r = 0.732, P < 0.001) and with the P‐MRI (r = 0.598, P < 0.001) scores. MRI and US data significantly correlated as to effusion (r = 0.819, P = 0.002), synovial hypertrophy (r = 0.633, P = 0.036) and cartilage erosion (r = 0.734, P = 0.010). Despite inherent limitations, joint US examination identified subclinical abnormalities of HJ in young subjects with severe HA.